Method for preparing negative electrode membrane by using semi-dry method, negative electrode membrane, secondary battery and electric device

By introducing negative electrode film forming additives in the preparation process of the negative electrode film of lithium-ion batteries to form SEI films, the problems of low battery energy density and reaction of PTFE with lithium ions in the prior art are solved, and the battery capacity and first effect are improved .

CN119495746APending Publication Date: 2025-02-21XIAOGAN CORNEX NEW ENERGY INNOVATION TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411673022.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The energy density of existing lithium-ion batteries is low, and the reaction of polytetrafluoroethylene (PTFE) in the dry electrode with lithium ions leads to a decrease in battery capacity.

Method used

The negative electrode film is prepared by the semi-dry method. By calculating the powder containing liquid electrolyte into a film, and adding negative electrode film-forming additives such as vinyl carbonate and fluorovinyl carbonate to form a stable electrolyte film (SEI) on the surface of the negative electrode. prevents PTFE from reacting with lithium ions.

Benefits of technology

It improves the discharge specific capacity and first effect of the battery, extends the service life of the battery, and reduces the loss of the internal resistance and energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119495746A_ABST
    Figure CN119495746A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a negative electrode film by using a semi-dry method, the negative electrode film, a secondary battery and an electric device. The negative electrode film-forming additive is introduced in the negative electrode material film-forming process through a semi-dry method, it is guaranteed that the film-forming additive is evenly distributed in the negative electrode material, in the first cycle process, the negative electrode film-forming additive preferentially reacts at a high potential to generate a polymer and a deposited lithium salt, and the surface of a negative electrode is coated with a layer of SEI film; therefore, the PTFE is prevented from reacting with lithium ions at a lower potential, and the capacity and the first effect of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a method for preparing a negative electrode film by a semi-dry method, a negative electrode film, a secondary battery and an electric device. Background Art

[0002] With the continuous development of lithium-ion batteries, new energy vehicles have become an important part of the passenger car and commercial vehicle markets. However, the range anxiety still hinders the further increase of new energy market share, and automobile companies are paying more and more attention to the energy density and production cost of lithium-ion batteries. Among them, the electrode is the fundamental factor affecting the energy density and the main cost of the battery.

[0003] At present, the main production method of lithium-ion battery electrodes is the wet process, which mixes active materials, binders, conductive agents and other materials in a solvent to obtain a slurry, and then coats and rolls the electrodes to obtain electrodes. Because the electrodes in the wet process need to be dried during the coating process, the solvent evaporates, resulting in more pores between the active materials and the conductive agent, making it difficult to increase the compaction density of the electrodes, resulting in low capacity density.

[0004] The dry process simplifies the materials and preparation processes, eliminates the solvent and coating drying steps, avoids the pores caused by solvent volatilization, and increases the compaction density by 10% to 30% compared to the wet-process electrode. It also saves material and process costs and reduces carbon emissions.

[0005] At present, dry-process electrodes use binders to fibrillate active materials and conductive agents to form self-supporting electrode films. Among them, polytetrafluoroethylene (PTFE) is often used as a dry-process electrode binder because of its stable bonding and strong processability. However, PTFE easily reacts with lithium ions in the negative electrode at low potential, consuming a large amount of active materials and causing a decrease in battery capacity. Summary of the invention

[0006] The present invention aims to solve one of the technical problems in the related art at least to a certain extent.

[0007] To this end, embodiments of the present invention provide a method for preparing a negative electrode film using a semi-dry method, a negative electrode film, a secondary battery, and an electrical device.

[0008] In a first aspect, the present invention provides a negative electrode membrane, which is obtained by rolling and pressing a powder containing a liquid electrolyte into a membrane, wherein a negative electrode film-forming additive is added to the liquid electrolyte.

[0009] Furthermore, the negative electrode film-forming additive first reacts at 1-2V and coats a layer of SEI film on the surface of the negative electrode.

[0010] Furthermore, the negative electrode film-forming additive includes one or both of vinylene carbonate and fluoroethylene carbonate.

[0011] In a second aspect, the present invention proposes a method for preparing the negative electrode film proposed in the first aspect by a semi-dry method, such as Figure 1 As shown, the following steps are included:

[0012] (a) mixing a conductive agent and a negative electrode active material uniformly to obtain a powder A;

[0013] (b) adding PTFE to the powder A, mixing at a low speed, and then completely shearing and fiberizing at a high speed to obtain powder B;

[0014] (c) adding a liquid electrolyte containing a lithium salt and a negative electrode film-forming additive to the powder B and mixing them evenly to obtain a powder C;

[0015] (d) rolling and pressing the powder C into a film to obtain a self-supporting electrode film.

[0016] In step (a), the conductive agent includes at least one of conductive carbon black, acetylene black, Ketjen black, lamellar graphite, graphene or carbon fiber, and the negative electrode active material includes at least one of natural graphite, artificial graphite, silicon carbon or silicon oxygen.

[0017] In step (b), PTFE is used as a dry electrode binder, and low-speed mixing is performed to allow PTFE and powder A to be fully mixed.

[0018] In step (c), the lithium salt is lithium hexafluorophosphate, and the liquid electrolyte is a mixture of EC:DMC:EMC in a volume ratio of 2:4:4.

[0019] Furthermore, the added amount of the conductive agent is 1% to 10% of the mass of the powder A.

[0020] The amount of the conductive agent added can be 1%, 3%, 5%, 7%, 9%, 10% of the mass of the powder A, or a value within a range consisting of any two values. When the amount of the conductive agent added is within a suitable range, the negative electrode has sufficient conductivity; when the amount of the conductive agent added is too much, the negative electrode energy density is low; when the amount of the conductive agent added is too little, it is difficult to form a conductive network, resulting in a decrease in electrical performance.

[0021] Furthermore, the added amount of the PTFE is 1% to 5% of the mass of the powder A.

[0022] The amount of PTFE added can be 1%, 2%, 3%, 4%, 5% of the mass of the powder A, or a value within a range consisting of any two values. When the amount of PTFE added is within a suitable range, the fibers can bond to each other to form a self-supporting membrane; when the amount of PTFE added is too much, the negative electrode energy density is low and the internal resistance is increased; when the amount of PTFE added is too little, the membrane adhesion is insufficient and it is easy to break.

[0023] Furthermore, the low-speed mixing is stirring at 150 to 1000 r / min for 5 to 10 min.

[0024] Furthermore, the high-speed complete shearing fiberization is stirring at 2000-5000 r / min for 10-20 min.

[0025] The purpose of high-speed complete shear fiberization is to allow the fibers to fully bond during the rolling process to form a self-supporting film.

[0026] Furthermore, the negative electrode film-forming additive includes one or both of vinylene carbonate and fluoroethylene carbonate.

[0027] Among them, the film formed by vinylene carbonate is an organic film, and the film formed by fluoroethylene carbonate is an inorganic film. When the negative electrode film-forming additive contains both vinylene carbonate and fluoroethylene carbonate, the inorganic film can ensure the transmission of lithium ions, and the organic film can ensure the isolation of PTFE from graphite electrons.

[0028] Furthermore, the amount of the negative electrode film-forming additive added is 1% to 20% of the mass of the liquid electrolyte.

[0029] The amount of the negative electrode film-forming additive added can be 1%, 5%, 10%, 15%, 20%, or a value within a range consisting of any two values. The amount of the negative electrode film-forming additive added is within a suitable range to form a stable electrolyte membrane; when the amount of the negative electrode film-forming additive added is too much, more active lithium will be consumed, and the electrolyte membrane will be unstable; when the amount of the negative electrode film-forming additive added is too little, the electrolyte membrane coating effect is insufficient.

[0030] In a third aspect, the present invention provides a secondary battery, comprising a negative electrode sheet, wherein the negative electrode sheet is obtained by rolling the negative electrode film provided in the first aspect or the negative electrode film prepared by the method provided in the second aspect onto a copper foil.

[0031] In a fourth aspect, the present invention provides an electrical device comprising the secondary battery provided in the third aspect.

[0032] Compared with the prior art, the beneficial effects of the present invention are:

[0033] The present invention introduces negative electrode film-forming additives into the film-forming process of negative electrode materials by a semi-dry method, so as to ensure that the film-forming additives are evenly distributed in the negative electrode materials. In the first cycle, the negative electrode film-forming additives are at a relatively high potential (1.0-2.0V vsLi / Li + ) preferentially reacts to form polymers and deposited lithium salts, coating the negative electrode surface with a SEI film, thereby preventing PTFE from reacting at lower potentials (0.3-0.55V vs Li / Li + ) reacts with lithium ions to improve battery capacity and initial efficiency.

[0034] The present invention adds an electrolyte containing a negative electrode film-forming additive during the semi-dry method for preparing a negative electrode film, so that the negative electrode film-forming additive preferentially forms a SEI film on the surface of the negative electrode active material, reduces the reaction between lithium ions and PTFE on the negative electrode surface, and improves the initial effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:

[0036] Figure 1 The present invention is a flow chart of the method for preparing a negative electrode membrane by a semi-dry method. DETAILED DESCRIPTION

[0037] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.

[0038] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.

[0039] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.

[0040] Example 1

[0041] S1: Prepare 3 g of conductive carbon black (SP), add it to 90 g of graphite, and mix well to obtain powder A.

[0042] S2: Prepare 2 g of polytetrafluoroethylene (PTFE) and add it to powder A. Mix at a low speed of 300 rpm for 8 min. Then stir at a speed of 2500 rpm for 15 min to complete high-speed shear fiberization of PTFE to obtain powder B.

[0043] S3: Prepare an appropriate amount of lithium hexafluorophosphate and dissolve it in a solvent with a volume ratio of EC:DMC:EMC of 2:4:4 so that the concentration of lithium hexafluorophosphate is 1 mol / L, and then add 1% by mass of vinylene carbonate (VC) and 10% by mass of fluoroethylene carbonate (FEC) to obtain a liquid electrolyte. Add 5g of the liquid electrolyte to powder B and mix well to obtain powder C.

[0044] S4: The powder C is rolled and pressed into a film to obtain a self-supporting electrode film with a thickness of 60 μm.

[0045] Example 2

[0046] S1: Prepare 3 g of conductive carbon black (SP), add it to 90 g of graphite, and mix well to obtain powder A.

[0047] S2: Prepare 2 g of polytetrafluoroethylene (PTFE) and add it to powder A. Mix at a low speed of 300 rpm for 8 min. Then stir at a speed of 2500 rpm for 15 min to complete high-speed shear fiberization of PTFE to obtain powder B.

[0048] S3: Prepare an appropriate amount of lithium hexafluorophosphate and dissolve it in a solvent with a volume ratio of EC:DMC:EMC of 2:4:4 so that the concentration of lithium hexafluorophosphate is 1 mol / L, and then add 1% by mass of vinylene carbonate (VC) and 5% by mass of fluoroethylene carbonate (FEC) to obtain a liquid electrolyte. Add 5g of the liquid electrolyte to powder B and mix well to obtain powder C.

[0049] S4: The powder C is rolled and pressed into a film to obtain a self-supporting electrode film with a thickness of 60 μm.

[0050] Example 3

[0051] S1: Prepare 3 g of conductive carbon black (SP), add it to 90 g of graphite, and mix well to obtain powder A.

[0052] S2: Prepare 2 g of polytetrafluoroethylene (PTFE) and add it to powder A. Mix at a low speed of 300 rpm for 8 min. Then stir at a speed of 2500 rpm for 15 min to complete high-speed shear fiberization of PTFE to obtain powder B.

[0053] S3: Prepare an appropriate amount of lithium hexafluorophosphate and dissolve it in a solvent with a volume ratio of EC:DMC:EMC of 2:4:4 so that the concentration of lithium hexafluorophosphate is 1 mol / L, and then add 1% by mass of vinylene carbonate (VC) and 15% by mass of fluoroethylene carbonate (FEC) to obtain a liquid electrolyte. Add 5g of the liquid electrolyte to powder B and mix well to obtain powder C.

[0054] S4: The powder C is rolled and pressed into a film to obtain a self-supporting electrode film with a thickness of 60 μm.

[0055] Example 4

[0056] S1: Prepare 3 g of conductive carbon black (SP), add it to 90 g of graphite, and mix well to obtain powder A.

[0057] S2: Prepare 2 g of polytetrafluoroethylene (PTFE) and add it to powder A. Mix at a low speed of 300 rpm for 8 min. Then stir at a speed of 2500 rpm for 15 min to complete high-speed shear fiberization of PTFE to obtain powder B.

[0058] S3: Prepare an appropriate amount of lithium hexafluorophosphate and dissolve it in a solvent with a volume ratio of EC:DMC:EMC of 2:4:4 so that the concentration of lithium hexafluorophosphate is 1 mol / L, and then add 10% by mass of vinylene carbonate (VC) to obtain a liquid electrolyte. Add 5g of the liquid electrolyte to powder B and mix well to obtain powder C.

[0059] S4: The powder C is rolled and pressed into a film to obtain a self-supporting electrode film with a thickness of 60 μm.

[0060] Comparative Example 1

[0061] S1: Prepare 3 g of conductive carbon black (SP), add it to 90 g of graphite, and mix well to obtain powder A.

[0062] S2: Prepare 2 g of polytetrafluoroethylene (PTFE) and add it to powder A. Mix at a low speed of 300 rpm for 8 min. Then stir at a speed of 2500 rpm for 15 min to complete high-speed shear fiberization of PTFE to obtain powder B.

[0063] S3: The powder B is rolled and pressed into a film to obtain a self-supporting electrode film with a thickness of 60 μm.

[0064] Comparative Example 2

[0065] S1: Prepare 3 g of conductive carbon black (SP), add it to 90 g of graphite, and mix well to obtain powder A.

[0066] S2: Prepare 2 g of polytetrafluoroethylene (PTFE) and add it to powder A. Mix at a low speed of 300 rpm for 8 min. Then stir at a speed of 2500 rpm for 15 min to complete high-speed shear fiberization of PTFE to obtain powder B.

[0067] S3: Prepare an appropriate amount of lithium hexafluorophosphate and dissolve it in a solvent with a volume ratio of EC:DMC:EMC of 2:4:4 so that the concentration of lithium hexafluorophosphate is 1 mol / L, and then add 0.1% by mass of vinylene carbonate (VC) and 0.1% by mass of fluoroethylene carbonate (FEC) to obtain a liquid electrolyte. Add 5g of the liquid electrolyte to powder B and mix well to obtain powder C.

[0068] S4: The powder C is rolled and pressed into a film to obtain a self-supporting electrode film with a thickness of 60 μm.

[0069] Test example

[0070] The dry-process negative electrode membranes prepared in Examples 1 to 4 and Comparative Examples 1 and 2 were assembled into lithium button cells. The separator was a PE film. The electrolyte was 1 mol / L lithium hexafluorophosphate dissolved in a solvent with a volume ratio of EC:DMC:EMC of 2:4:4. The amount of electrolyte added was 1.5 g / Ah. Charge and discharge were performed at 0.1 C. The test results are shown in Table 1 below.

[0071] Table 1:

[0072] Discharge specific capacity (mAh / g) First effect (%) Example 1 298.7 89.4 Example 2 292.4 86.1 Example 3 293.9 85.3 Example 4 294.4 86.7 Comparative Example 1 283.6 83.4 Comparative Example 2 284.3 83.5

[0073] According to Table 1, by comparing Examples 1 to 4 and Comparative Example 1, it can be seen that after adding the negative electrode film-forming additive, the discharge specific capacity and the first effect are significantly improved. The negative electrode film-forming additive added in Examples 1 to 4 can preferentially obtain electrons to form a SEI film, thereby preventing the reaction between PTFE and lithium ions on the negative electrode surface and increasing the first effect.

[0074] By comparing Examples 1 to 4 and Comparative Examples 1 and 2, it can be seen that when no negative electrode film-forming additive is added or the amount of negative electrode film-forming additive added is too small during the preparation of the negative electrode film, the discharge specific capacity and the first efficiency of the battery cannot be improved.

[0075] The present invention adds a negative electrode film-forming additive during the preparation of the negative electrode film, and the discharge specific capacity and the first efficiency of the battery are relatively high. Adding the negative electrode film-forming additive during the preparation of the negative electrode film can better ensure that the additive is evenly distributed in the electrode sheet, thereby forming a uniform SEI film coated on the negative electrode surface during the first cycle.

[0076] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms may be for different embodiments or examples. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.

[0077] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0078] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.

Claims

1. A negative electrode film, characterized in that: The electrolyte is obtained by rolling and pressing a powder containing a liquid electrolyte into a film, wherein a negative electrode film-forming additive is added to the liquid electrolyte.

2. The negative electrode film according to claim 1, characterized in that The negative electrode film-forming additive first reacts at 1-2V and coats the negative electrode surface with a layer of SEI film.

3. The negative electrode film according to claim 2, characterized in that: The negative electrode film-forming additive includes one or both of vinylene carbonate and fluoroethylene carbonate.

4. A method for preparing a negative electrode film using a semi-dry method, characterized in that: The method for preparing the negative electrode film according to any one of claims 1 to 3 comprises the following steps: (a) mixing a conductive agent and a negative electrode active material uniformly to obtain a powder A; (b) adding PTFE to the powder A, mixing at a low speed, and then completely shearing and fiberizing at a high speed to obtain powder B; (c) adding a liquid electrolyte containing a lithium salt and a negative electrode film-forming additive to the powder B and mixing them evenly to obtain a powder C; (d) rolling and pressing the powder C into a film to obtain a self-supporting electrode film.

5. The method according to claim 4, characterized in that The added amount of the conductive agent is 1% to 10% of the mass of the powder A; And / or, the added amount of the PTFE is 1% to 5% of the mass of the powder A.

6. The method according to claim 4, characterized in that The low speed mixing is stirring at 150-1000 r / min for 5-10 min.

7. The method according to claim 4, characterized in that The high-speed complete shearing fiberization is carried out by stirring at 2000-5000 r / min for 10-20 min.

8. The method according to claim 4, characterized in that The amount of the negative electrode film-forming additive added is 1% to 20% of the mass of the liquid electrolyte.

9. A secondary battery, characterized in that: The invention comprises a negative electrode sheet, wherein the negative electrode sheet is obtained by rolling the negative electrode film according to any one of claims 1 to 3 or the negative electrode film prepared by the method according to any one of claims 4 to 8 onto a copper foil.

10. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to claim 9.

Citation Information

Patent Citations

  • Porous pole piece manufacturing method and lithium ion battery

    CN116111049A

  • Semi-solid lithium ion battery and preparation method thereof

    CN118040074A

  • Negative electrode for lithium ion secondary battery, method for manufacturing the same, and secondary battery including the same

    JP2014137861A

  • Lithium secondary battery anode having improved electrochemical characteristics by dry process and electrode additive content adjustment, method for manufacturing same, and lithium secondary battery comprising same

    WO2024232460A1

  • KR20240164556A